The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/1520-6807(198301)20:1<59::aid-pits2310200114>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Intervening with school problems: A family systems perspective

Abstract: Viewing children's behavior from a systems perspective allows the school-based consultant an expanded perception of the contextual function of the behavior. The two key systems in a child's life, home and school, often overlap, and what occurs in one system can affect the child's behavior in the other system. By considering the relationships of the child to both home and school, a more holistic view of the child is obtained, and greater opportunity for family involvement is provided. This article explains the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Family participation as a unit in the assessment process has been found to be effective both in terms of client satisfaction and in terms of following through on decisions (Freund, 1982). Fine andHolt (1983), Friedman (1978), and Selig and Berdie (1981) present various strategies and guidelines to map the family's transactional patterns and to assess the function that learning disability or other handicaps have in any given family.…”
Section: Assessmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Family participation as a unit in the assessment process has been found to be effective both in terms of client satisfaction and in terms of following through on decisions (Freund, 1982). Fine andHolt (1983), Friedman (1978), and Selig and Berdie (1981) present various strategies and guidelines to map the family's transactional patterns and to assess the function that learning disability or other handicaps have in any given family.…”
Section: Assessmentmentioning
confidence: 94%
“…School represents the second key system (Fine & Holt, 1983) in understanding the child's learning behavior or learning difficulties. A classroom observation is a necessary part of the assessment.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate ecosystemic intervention in the present situation (on the basis of the above analysis), would have to take account of the need for John and his mother to be involved in a collaborative relationship, with the mother providing support for John. In similar circumstances, reported in the literature, where school problems are seen in terms of the interaction between the family and the school system, the first stage in developing an intervention strategy is the family-school interview (Aponte 1976, Fine and Holt 1983, Power and Bartholomew 1985. This is usually organised by a consultant family therapist.…”
mentioning
confidence: 90%
“…The school psychology literature increasingly has focused on the need to broaden the role of psychologists in the schools beyond that of traditional psychoeducational assessment. Some have suggested that one strategy school psychologists may employ in an attempt to accomplish role diversification is to increase the extent of their involvement with parents (Anderson, 1983;Fine & Holt, 1983). The importance of the family system in behavior change is evident (e.g., Anderson, 1983) and provides additional rationale for school psychologists and parents to work together.…”
mentioning
confidence: 99%